Identificar trastornos visuales en pacientes portadores de VIH. - Tapia Montoya, Nataly Marina (2020)
HIV (human immunodeficiency virus) began in the United States in 1981, it is the causative agent of AIDS (acquired immunodeficiency syndrome). This virus affects both men and women and is a very important cause of mortality in young adults. This virus is characterized by the destruction of the immune system, especially CD4 lymphocytes, which are the ones that help fight infections that enter our body. Around 30 to 70% of patients with AIDS may present some type of ophthalmological complication, among the most frequent ocular manifestations are: vascular microangiopathy, cytomegalovirus retinitis and Kaposi's sarcoma. For this reason, the objective of the optometrist is to provide primary care and in the case of any pathological manifestation to refer to ophthalmological support in time. A 65-year-old female patient attends an optometric consultation referring to decreased visual acuity both from far and near, a situation that prevents her from comfortably performing close activities, and with a diagnosis of HIV approximately one year ago. Subjective refraction and objective examinations by means of biomicroscopy and assessment of the posterior segment were the main diagnostic measures that were performed to rule out ocular alterations due to HIV. Where no type of alteration of the ocular system was found and its decrease in visual acuity was due to myopia accompanied by presbyopia due to age.